Establishing achievable benchmarks for quality improvement in systemic therapy for early‐stage breast cancer. Issue 19 (5th July 2017) - Powis, Melanie; Sutradhar, Rinku; Gonzalez, Alejandro; Enright, Katherine A.; Taback, Nathan A.; Booth, Christopher M.; Trudeau, Maureen; Krzyzanowska, Monika K.
Abstract : BACKGROUND: Setting realistic targets for performance is a consistent challenge in quality improvement. In the current study, the authors used administrative data to define achievable targets for a panel of 15 previously developed quality indicators (QIs) focusing on systemic therapy in patients with early‐stage breast cancer. METHODS: Deterministically linked administrative databases were used to identify patients with TNM stage I to stage III breast cancer who were diagnosed between 2006 and 2010 in Ontario, Canada. For each individual indicator, data‐driven empirical benchmarks were calculated using the pared‐mean benchmark approach. Variation in institution‐level performance for each indicator was examined through the construction of funnel plots. RESULTS: A total of 28, 303 patients with early‐stage breast cancer were identified, 43% of whom received adjuvant chemotherapy. For the 9 QIs for which receiving the service or outcome was desirable (ie, consultation with a medical oncologist), the benchmark varied from 40.9% to 100%. For the 6 indicators for which not receiving the service or outcome was desirable (ie, incidence of febrile neutropenia), the benchmark varied from 0% to 49.0%. There was substantial variation noted with regard to the number of institutions meeting the target and the amount of interinstitution variation between the QIs. Top performing institutions varied by indicator, with no individual institution meeting the benchmark for all indicators. For the majority of indicators, institution size was not found to be correlated with performance. CONCLUSIONS: Data‐derived benchmarking can be used to facilitate quality improvement by identifying areas of both good as well as suboptimal performance while defining an achievable target for which to strive. Cancer 2017;123:3772–3780. © 2017 American Cancer Society Abstract : Data‐derived benchmarking can be used to facilitate quality improvement by defining an achievable target for which to strive. Benchmarking helps to identify areas of good performance as well as potential targets for quality improvement initiatives.